Clinical InvestigationsPreoperative high dose rate brachytherapy for clinical stage II endometrial carcinoma - Shukla, Gaurav; Beriwal, Sushil; C. Krivak, Thomas; Kelley, Joseph L.; Sukumvanich, Paniti; Edwards, Robert P.; Richard, Scott; Olawaiye, Alexander; Zorn, Kristin K. (Journal of Contemporary Brachytherapy, 2011)
Purpose : We sought to evaluate pathological response, tolerance, and outcome after preoperative (neoadjuvant) high dose rate brachytherapy in a small series of patients with clinical stage II endometrial carcinoma, and to evaluate a dose and fractionation protocol for this treatment. Material and methods : Twelve women diagnosed with clinical stage II endometrial carcinoma from 1999-2010 were treated with preoperative radiation therapy. Their medical charts were retrospectively analyzed for HDR treatment regimen, pathological response, and longitudinal outcomes. Radiation doses were normalized to a biologically equivalent dose of 2 Gy per fraction (EQD2). Results : Two patients had complete pathological response to neoadjuvant therapy; five more had only microscopic residual disease at the time of surgery. At a median follow up of 37 months (1-91 months), one patient has developed recurrence at the vaginal apex six months after completing initial therapy, while another developed a lung recurrence at 28 months. Two-year disease-free and cause-specific survivals were 88% and 100%, respectively. Conclusions : Our small study shows that the HDR fractionation schedule, as done in our series for preoperative radiation therapy for clinical stage II endometrial cancer, is well tolerated and would be an option for patients treated with neoadjuvant radiation therapy.